EVALUATION OF THE RELATIONSHIP BETWEEN MORPHOLOGICAL CHARACTERISTICS AND PULLOUT RESISTANCE OF LIVE CUTTINGS OF Phyllanthus sellowianus (Klotzsch) Müll.Arg. - Maffra, Charles Rodrigo Belmonte; Sousa, Rita dos Santos; Pinheiro, Rinaldo José Barbosa; Sutili, Fabrício Jaques (Floresta, 2021)
This study aimed to evaluate the interdependence between the morphological characteristics and the pullout resistance of live cuttings of Phyllanthus sellowianus. Vertical pullout tests and shoot and root diameter and length measurements were performed in 144 live cuttings, with 2.5 cm in diameter and 50 cm in length, planted in 1x1 m spacing. The evaluations were performed at 60, 133, 186, 252, 320, and 421 days after planting, and the differences between mean growth and vertical pullout resistance values were analyzed using the Tukey test and linear regression equations. The plants showed the highest mean total shoot length (875 cm), total root length (405 cm), and vertical pullout resistance (1.5 kN) values between 252 and 421 days after planting. The plants increased their pullout resistance at an average rate of 0.20 kN/month in the most favorable growth periods, followed by average increments in the total shoot and root length of 118.4 and 57.1 cm/month, respectively. The pullout resistance showed positive correlations with all above- and below-ground morphological characteristics tested, but it was best explained by the cross-sectional area of shoots (mm²) which showed r² = 0.55. The biometric variables of P. sellowianus propagated from cuttings generally explained up to half of the variations in the species’ pullout resistance.